Comparison of mannheim peritonitis index and revised multiple organ failure score in predicting mortality and morbidity of patients with secondary peritonitis - Pattanaik, S. K.; John, A.; Kumar, V. A. (International Surgery Journal, 2017)
Background: Secondary peritonitis carries high mortality and morbidity. Many scoring systems have been designed to assess its severity. This study was undertaken to compare the Mannheim peritonitis index (MPI) and revised multiple organ failure score (Revised MOFS) in predicting the mortality and morbidity. Methods: A prospective observational study was undertaken in adults operated for gastrointestinal perforation. Clinical and biochemical parameters as required for MPI and Revised MOFS were recorded. Each of the scores were divided under four categories; MPI <14, 14-21, 22-29 and >29; Revised MOFS 0, 1, 2 and >2. Data was compared for predicting mortality and morbidity. P-value, ROC curve and 95% CI were used as statistical tools. Results: Two thirds of 120 patients studied presented after 48 hours. MPI score of <14, 14-21, 21-29 and >29 had mortality of 0%, 2.2%, 27.2% and 50% respectively. ROC curve showed highest sensitivity and specificity of 79% and 70% respectively at MPI of 25. Significant value for mortality was obtained with MPI >25 (p= 0.000012) and with Revised MOFS >1 (p< 0.001); for morbidity with MPI >21 (p= 0.010) and with Revised MOFS >1 (p< 0.001). 20% patients with Revised MOFS zero were also morbid. Conclusions: Both MPI and Revised MOFS systems are good in predicting the mortality, but MPI is easy scoring system and a better option for predicting morbidity. MPI score >25 for mortality and >21 for morbidity are significant.